Pengaruh Literasi Keuangan Syariah dan Inklusi Keuangan Syariah Digital Pada Sektor Pertanian - Buono, Kulup Bina; Noviarita, Heni; Iqbal, Muhammad (Jurnal Ilmiah Ekonomi Islam, 2023)
The agricultural sector remains one of the main pillars in supporting food security and economic growth in many countries. However, access to financial services in the agricultural sector is relatively low. One of the main factors causing problems in the agricultural sector is the low level of financial literacy and inclusion. The aim of this study is to analyze what factors influence the level of financial literacy and inclusion in the agricultural sector. This study is a descriptive qualitative study with a library research method, namely reviewing and re-analyzing previous research related to financial literacy and inclusion in the agricultural sector. From the results of the analysis, it was found that the factors inhibiting sharia financial literacy and inclusion in the agricultural sector were the level of education, access to sharia financial institutions in rural areas, and low public awareness. The factors in this study are still limited, so it is hoped that there will be more extensive development in further research.